PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI: STUDI PADA POLITEKNIK PEMBANGUNAN PERTANIAN MALANG - Farah Adiba; Diana Rosita (STIA MALANG, 2023)
The research aims to find out whether there is any significant correlation between compensation, andperformance mediated by motivation in the Agricultural Development Polytechnic Malang. This research used aqualitiative method. The data was collected using questionnaire, and the technique used in taking the sample wasStratified Random Sampling. The sample comprised all employee Agricultural Development Polytechnic Malang.The total respondents were 104 people. The data analysis was conducted using Partial Least Square (PLS)Method by employing 3.0 SmartPLS program. The research results showed that all the hypotheses put forwardwere corroborated except the one dealing with motivation. motivation did not have a significant effect on employeeperformance because the existence of some compensation in the form of self-development is not felt by allemployees. In addition, compensation in the form of self-development is often not in accordance with the needs ofemployees. While work motivation has a role as a mediating variable on the effect of compensation on employeeperformance. Thus it can be said that motivation bridges the effect of compensation on employee performance.